Anthropology at an Intersection: A report from 'Relations and beyond: conference of the Finnish Anthropological Society' - Wilenius, Heikki (Suomen Antropologi: Journal of the Finnish Anthropological Society, 2023)
The Conference of the Finnish Anthropological Society, held in Rovaniemi, a few kilometres south of the Arctic Circle, marked my return to the realm of face-to-face scholarly gatherings since the start of the pandemic. Taking part in the fervent exchange of ideas and copious discussions was a riveting experience. All this transpired within the cramped hall-ways of Arktikum, a peculiar architectural amalgam of 1930s totalitarian art deco and utopian glass domes, a seemingly unsuitable venue for an assembly of roughly 300 anthropologists. Yet, despite the spatial constraints, the deft conference team pulled off a remarkable feat, orchestrating a successful affair. It was an environment teeming with off-script encounters and incessant confabulation. After several years of screen-mediated anthropology, the intensity of it all felt intoxicating.